Primary school pupils cognitive abilities in informatics - Dagienė, Valentina; Feiferytė, Simona; Sutkutė, Elena (Lietuvos matematikos rinkinys, 2014)
In Europe intensively are searching for opportunities to promote informatics as a fundamental subject teaching of elementary schools, beginning from primary classes. Looking for ways how to do it. Informatics and information technology contest’s “Beaver” scientific community has started to arrange tasks for primary school’s pupils. In Lithuania already for two years contest had attracted many of the 3rd and 4th grade pupils. Contest’s tasks and pupils’ solutions have been taken to analyse, in order to improve infants’ Informatics cognitive abilities. This article discusses the results of an expert evaluation of informatics tasks for primary school pupils and analyses the results of participants.
Keywords: informatics; primary education; cognitive abilities; contests; problem solving